The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2009
DOI: 10.2741/3449
|View full text |Cite
|
Sign up to set email alerts
|

Molecular characterization of Ehrlichia interactions with tick cells and macrophages

Abstract: Several tick-transmitted Anaplasmataceae family rickettsiales of the genera Ehrlichia and Anaplasma have been discovered in recent years. Some are classified as pathogens responsible for emerging diseases and are a growing health concern for people. These illnesses include human monocytic ehrlichiosis, human granulocytic ewingii ehrlichiosis and human granulocytic anaplasmosis which are caused by Ehrlichia chaffeensis, E. ewingii and Anaplasma phagocytophilum, respectively. Despite the complex cellular environ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
19
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 84 publications
2
19
0
1
Order By: Relevance
“…Adenine, the base found at the transcription start site for genes 14 and 19 of E. chaffeensis , appears to be the most common base at which transcription is initiated from rickettsiales genes, including pathogens of the genera Rickettsia and Anaplasma [31-34]. Our previous studies and those of other investigators also support that genes 14 and 19 are transcriptionally active independent of E. chaffeensis originating from macrophages or tick cells [9,19,21,35-38]. In the current study, quantitative RT-PCR analysis confirmed the previous observations about the presence of messages for genes 14 and 19 in both host cell backgrounds.…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…Adenine, the base found at the transcription start site for genes 14 and 19 of E. chaffeensis , appears to be the most common base at which transcription is initiated from rickettsiales genes, including pathogens of the genera Rickettsia and Anaplasma [31-34]. Our previous studies and those of other investigators also support that genes 14 and 19 are transcriptionally active independent of E. chaffeensis originating from macrophages or tick cells [9,19,21,35-38]. In the current study, quantitative RT-PCR analysis confirmed the previous observations about the presence of messages for genes 14 and 19 in both host cell backgrounds.…”
Section: Discussionsupporting
confidence: 67%
“…Recently, we reported that Ehrlichia species alter the expression of many proteins in a host cell-specific manner [18-21]. Differentially expressed proteins include outer membrane proteins made from p28-Omp multigene locus having 22 tandomly arranged paralogous genes of E. chaffeensis [18-20].…”
Section: Introductionmentioning
confidence: 99%
“…Evaluation of different E. chaffeensis isolates demonstrated a differentially expression of p28/30-Omp proteins in infected macrophages and tick cell cultures. In infected macrophages, the dominant E. chaffeensis expressed proteins are the products of the p28-Omp 19 and 20 genes (40, 41). In cultured tick cells derived from E. chaffeensis vector, Amblyomma americanum and non-vector ( Ixodes scapularis ) ticks, E. chaffeenesis expression consists only of the p28-Omp 14 protein (40, 41).…”
Section: Microbiologymentioning
confidence: 99%
“…In infected macrophages, the dominant E. chaffeensis expressed proteins are the products of the p28-Omp 19 and 20 genes (40, 41). In cultured tick cells derived from E. chaffeensis vector, Amblyomma americanum and non-vector ( Ixodes scapularis ) ticks, E. chaffeenesis expression consists only of the p28-Omp 14 protein (40, 41). It is postulated that this differential expression of proteins within the p28/p30-Omp locus may be critical for the adaptation of Ehrlichia species to their different hosts (mammals and ticks).…”
Section: Microbiologymentioning
confidence: 99%
“…Later in the developmental cycle, RBs convert back to EBs, which are released from infected cells [12,14]. The transformation of RBs to EBs by E. chaffeensis is observed in both vertebrate and tick hosts [15]. …”
Section: Introductionmentioning
confidence: 99%